A theoretical framework of considering urban green spaces as a factor determining house price in Kuala Lumpur - Manzahari, Mohd Nasrul Hanis; Asmawi, M. Zainora; Hj. Mohd. Noor, Norzailawati (2014)
There is a significant loss of green space happening in Kuala Lumpur to pave the way for more built up developments, resulting in population losing more than a few shrubs on the ground. The situation raises the question on the importance of green spaces towards the planning implementation and development decision. As there are mixed evidences on the existence of relationship between green spaces and house price, the literatures present that the relationship can be proved through statistical and spatial analysis. Thus, this paper mainly focuses on the theoretical framework of considering green spaces as a factor determining house price in Kuala Lumpur. It is important to consider various understandings of green spaces as well as housing price, their sub-types as well as literatures related to them. Several steps have been carried out during the preliminary study which includes literature review, questionnaire survey, site observation and GIS application. Based on the previous studies, the existence of relationship between green spaces and housing price is proven through hedonic theory model and utilization of Geographical Information System (GIS). In estimating green spaces as a factor determining house price in Kuala Lumpur, the definition of green spaces has been narrowed down to open spaces, a sub-type of green spaces due to fact that open spaces are easier to recognized and surveyed. The effect of green spaces in determining house price can be surveyed by analyzing the relationship between the proximity of open space from specific house with the offer price surveyed from the house owner through questionnaire forms. The utilization of GIS assists in providing a reliable set of results which requiring the availability of information on existing land use, urban pattern identification and computation of landscape metrics. This paper has identified significant point which is - it is possible for green spaces to influence the house pricing in Kuala Lumpur. The theoretical framework and methods presented in this paper appear practical, workable and reasonable to obtain reliable results in future stages of the research.